2021
DOI: 10.1093/cid/ciab688
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Coronavirus Disease 2019 (COVID-19) on Healthcare-Associated Infections

Abstract: Background The profound changes wrought by COVID-19 on routine hospital operations may have influenced performance on hospital measures, including healthcare-associated infections (HAIs). We aimed to evaluate the association between COVID-19 surges and HAI and cluster rates. Methods In 148 HCA Healthcare-affiliated hospitals, 3/1/2020-9/30/2020, and a subset of hospitals with microbiology and cluster data through 12/31/2020, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
173
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(190 citation statements)
references
References 17 publications
12
173
1
4
Order By: Relevance
“…The COVID-19 pandemic put a massive burden on the healthcare system, leading to changes in standard patient care approaches, increasing the incidences of hospital-acquired infections (HAIs). This additional COVID-19 burden, and long-term treatment of the associated patients, may have a significant association with HAIs [ 5 ]. The research community of AMR observed the transmission of SARS-CoV-2 and its interaction with other diseases worldwide, especially with secondary bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic put a massive burden on the healthcare system, leading to changes in standard patient care approaches, increasing the incidences of hospital-acquired infections (HAIs). This additional COVID-19 burden, and long-term treatment of the associated patients, may have a significant association with HAIs [ 5 ]. The research community of AMR observed the transmission of SARS-CoV-2 and its interaction with other diseases worldwide, especially with secondary bacterial infections.…”
Section: Introductionmentioning
confidence: 99%
“…At the beginning of the pandemic, several publications proposed new organizations to manage COVID-19 patients and separate them from other emergencies [19][20][21][22][23][24]. After a few times, several surgical and medical specialties, such as bacteriologists, neurologists and oncologists, warned about the side effects of usual medical pathway disorganization [25][26][27][28].…”
Section: Plos Onementioning
confidence: 99%
“…There were also 24% more multidrug-resistant-organism infections. Higher COVID-19 discharge rates were associated with higher rates of hospital-acquired and multidrug-resistant organism infections ( 1 ).…”
Section: Introductionmentioning
confidence: 99%